The economic war against Cuba A Historical and Legal Perspective on the U.S. Blockade - Salim Lamrani (New York New York, 2013)
It is impossible to fully understand Cuba today without also understanding
Includes bibliographical references (pages 115-120) and index
Keywords: Economic sanctions, American--Cuba--History--20th century